Sustainability Compass Analysis of the Primadona Tuban Program through the SDGs (Sustainability Development Goals) Indicator - Maryani; Hudaya, Muhammad Reza; Hadi Sucipto, Tinoto; Fitriani Wira Kurniawati, Anita; Martiana Nugraha, Puput; Maulidiyatul Jannah, Nella; Wahyu Indriyani, Dina (Prospect Publishing, 2024)
The Primadona Tuban is a CSR program that aims to solve environmental, economic, social, and community welfare problems. This research describes the impacts that occurred in society after the implementation of the Primadona Tuban Program. Discussion of impacts is carried out using a sustainable compass analysis consisting of nature, economic, society, and well-being. Researchers operate a sustainability compass using 17 SDGs indicators. The research results show that the Primadona Tuban Program has had an impact on nature in the form of planting 3 types of trees, carbon absorption of 483.2 g/hour, managing vegetation cover, and handling climate change. The economic impact that occurs is improving the group's economy through tourism activities and marine product management, infrastructure development, increasing marine protein consumption by 25%, and collaboration between groups to achieve goals. The social impact of this program is gender equality with the involvement of 2 groups of women in public spaces, access to clean water and proper sanitation, reduced inequality through access to entrepreneurship for vulnerable groups, safe settlements from disasters and strong institutions in managing Panduri Beach. The wellbeing that arises from this program is a reduction in poverty, no hunger, and a healthy and prosperous life.